2014
DOI: 10.1007/s11010-014-2110-7
|View full text |Cite
|
Sign up to set email alerts
|

EOLA1 protects lipopolysaccharide induced IL-6 production and apoptosis by regulation of MT2A in human umbilical vein endothelial cells

Abstract: Endothelial cell (EC) injury or dysfunction is believed to be mediated at least in part by lipopolysaccharide (LPS). Recent studies have shown that LPS induces apoptosis in different types of endothelium, including HUVEC. Previously we used EOLA1 (endothelial-overexpressed LPS-associated factor 1) cDNA as a bait and performed a yeast two-hybrid screening of a human liver cDNA library and identified metallothionein 2a (MT2a) as the associated protein. EOLA1 protein plays a role as a signal transduction factor. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…EOLA1 is weakly expressed under the steady condition and highly expressed in response to LPS in ECV304 cells. The discovery of the protein association between EOLA1 and metallothionein 2A (MT2A) has been confirmed by yeast double-hybridization and coimmunoprecipitation assay [ 2 , 5 ]. MT2A is known to have anti-inflammatory, antiendotoxin, and tumor-inhibiting effects in cell cultures [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…EOLA1 is weakly expressed under the steady condition and highly expressed in response to LPS in ECV304 cells. The discovery of the protein association between EOLA1 and metallothionein 2A (MT2A) has been confirmed by yeast double-hybridization and coimmunoprecipitation assay [ 2 , 5 ]. MT2A is known to have anti-inflammatory, antiendotoxin, and tumor-inhibiting effects in cell cultures [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial-overexpressed lipopolysaccharide (LPS)-associated factor 1 (EOLA1) interacts with MT2A in ECV304 cells 18 . This group also found that EOLA1 regulated MT2A to modulate HUVEC apoptosis during inflammatory responses 19 . In addition, in esophageal cancer cells, the interaction of esophageal cancer related gene 2 (ECRG2) and MT2A was suggested to play an important role in the carcinogenesis of esophageal cancer; ECRG2 co-localizing with MT2A was mostly in nuclei and slightly in cytoplasm 20 .…”
Section: Discussionmentioning
confidence: 94%
“…Metallothioneins are present in multiple tissues and mainly consist of 4 groups: metallothionein-1A, metallothionein-2, metallothionein-3, and metallothionein-4. It has been reported that metallothionein-2 serves as a critical regulator of numerous cell activities, including differentiation, apoptosis, autophagy, immune response, carcinogenesis, and drug resistance (28,(46)(47)(48)(49)(50). The effects of metallothionein-2 on pathophysiological processes, particularly inflammation, are subjects of many studies (51).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of metallothionein-2 on pathophysiological processes, particularly inflammation, are subjects of many studies (51). A study by Liu et al showed that metallothionein-2 knockdown increased LPS-induced IL-6 production in endothelial cells (49), indicating a protective role against inflammatory responses. Takano and colleagues demonstrated that transgenic mice with metallothionein overexpression were more resistant to neutrophilic lung inflammation and lung edema induced by intratracheal challenge with LPS (52).…”
Section: Discussionmentioning
confidence: 99%